"I must do this!": A latent profile analysis approach to understanding the role of irrational beliefs and motivation regulation in mental and physical health. Issue 8 (18th April 2022) - Turner, M. J.; Miller, A.; Youngs, H.; Barber, N.; Brick, N. E; Chadha, N. J.; Chandler, C.; Coyle, M.; Didymus, F. F.; Evans, A. L.; Jones, K.; McCann, B.; et al.
ABSTRACT: In the research concerning rational emotive behaviour therapy (REBT) in sport and exercise, irrational beliefs are proposed as a risk factor for health. Concurrent to this, researchers have also indicated that autonomous and controlled motivation, as proposed in organismic integration theory could, together with irrational beliefs, determine individual health. However, research is yet to align irrational beliefs and motivation, and explore how this alignment relates to mental health. The present two study paper identifies individual subgroups, drawn from data concerning irrational beliefs, motivation, and health (psychological distress, and physical health), in a sample of exercisers (study 1) and student athletes (study 2). We examined the latent profile structure of irrational beliefs and motivation, and how these latent profiles relate to psychological distress (studies 1 and 2), and physical health (study 2). Results indicate a two class profile whereby class 1 is characterised by high irrational beliefs, low self-determined motivation, and poor health outcomes. Class 2 is characterised by low irrational beliefs, high self-determined motivation, and better health outcomes. The findings are discussed in relation to the theoretical implications for REBT and organismic integration theory, and the practical implications for key stakeholders in the health of exercise participants and athletes.